2022
DOI: 10.7759/cureus.30491
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Autotransplantation as an Alternative Biological Treatment: A Literature Review

Abstract: Tooth autotransplantation is the treatment modality in which a tooth is transferred from one site to another in the same person. This technique has a history of centuries. However, it is not well-known or welldocumented. Essential aspects of the clinical procedure, criteria for performing tooth autotransplantation, advantages, disadvantages, and complications are also discussed in the review. It has been a public health concern considering the prevalence of dental trauma in children, the financial burden of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
7
0
2
Order By: Relevance
“…Although the survival and success of a tooth transplant are influenced by numerous variables, 3 maintenance of a healthy periodontal ligament is of primary importance. 2,17 The average autotransplantation success rate is reported to exceed 80% if the root of the transplant is immature at the time of surgery, with the ideal root developmental stage suggested to be one-half to three-quarters of the normal root length using Moorrees' root classification. 47,48 A premolar tooth with sufficiently long roots (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the survival and success of a tooth transplant are influenced by numerous variables, 3 maintenance of a healthy periodontal ligament is of primary importance. 2,17 The average autotransplantation success rate is reported to exceed 80% if the root of the transplant is immature at the time of surgery, with the ideal root developmental stage suggested to be one-half to three-quarters of the normal root length using Moorrees' root classification. 47,48 A premolar tooth with sufficiently long roots (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…desirable rootto-crown ratio), yet still has an open apex at the time of autotransplantation is an ideal donor candidate, as there is still enough room at the apex for revascularization. 2 It has been suggested that the ideal age for transplanting premolars is approximately 12 years of age, 25 as the completion of root development of these teeth has been reported to occur around 13-14 years of age. 49 Despite this suggestion, this case series demonstrates favourable autotransplantation outcomes in patients ranging in age from 9 years and 5 months to 13 years old at the time of the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations